Transverse dentoalveolar changes of mandibular canine and premolar regions after lip bumper therapy: a retrospective CBCT study - Li, Jiahui; Boucher, Normand S.; Chung, Chun-Hsi; Shah, Shalin; Li, Chenshuang (Frontiers in Oral Health, 2025)
ObjectivesLip bumpers (LB) treatment has been used to expand the mandibular arch during mixed dentition. The aim of this study is to evaluate the effects of LB on the mandibular transverse changes in the canine and premolar regions using CBCT.Materials and methodsThis retrospective study utilized pre- (T1) and post-treatment (T2) CBCT images from the children who were treated either with rapid maxillary expander (RME) alone (RME group) or with RME and lip bumpers (RME + LB group) for interceptive orthodontic treatment. The T1 (pre-interceptive orthodontic treatment evaluation) and T2 (pre-comprehensive orthodontic treatment evaluation) CBCT images from the children who did not go through the interceptive orthodontic treatment were used as control. The CBCT images were oriented according to the occlusal plane and the three-dimensional superimposition on the mandible of T1 and T2 images was performed in the Dolphin 3D software, followed by a series of dental and alveolar linear and angular measurements. Only the mandibular canine and premolar regions with solid primary teeth that showed root structure below the furcation bilaterally at T1 and permanent teeth fully erupted in occlusion bilaterally at T2 were included. The intergroup comparisons were performed using the Mann–Whitney U test.ResultsAs the control group did not have a sufficient number of subjects after excluding the non-qualified regions, the following comparisons were only performed and reported between the RME group and the RME + LB group. RME + LB group (n = 30, 9.00 ± 0.86 years old at T1, 11.99 ± 0.59 years old at T2) showed significantly more bodily buccal movement of mandibular canines and premolars than the RME group (n = 25, 8.72 ± 0.88 years old at T1, 12.00 ± 0.96 years old at T2), but inter-mandibular buccal surface width increase was only observed in the second premolar region. In addition, the RME + LB groups showed less buccal alveolar bone thickness and height than the RME group in the mandibular canine and first premolar regions.ConclusionLB significantly expanded the mandibular transverse dimension dentally, with permanent canine and premolars erupting more buccally. However, it does not increase the skeletal transverse dimension of the alveolar bone at the canine and first premolar regions. Further studies are needed to evaluate the long-term effects of LB.